An Alternative Approach to Water Regulations for Public Health Protection at Bathing Beaches. (29th January 2013) - Abdelzaher, Amir M.; Solo-Gabriele, Helena M.; Phillips, Matthew C.; Elmir, Samir M.; Fleming, Lora E.
Abstract : New approaches should be considered as the US Environmental Protection Agency (EPA) moves rapidly to develop new beach monitoring guidelines by the end of 2012, as these guidelines serve as the basis by which states and territories with coasts along the oceans and Great Lakes can then develop and implement monitoring programs for recreational waters. We describe and illustrate one possible approach to beach regulation termed as the "Comprehensive Toolbox within an Approval Process (CTBAP)." The CTBAP consists of three components. The first is a "toolbox" consisting of an inventory of guidelines on monitoring targets, a series of measurement techniques, and guidance to improve water quality through source identification and prevention methods. The second two components are principles of implementation. These include first, "flexibility" to encourage and develop an individualized beach management plan tailored to local conditions and second, "consistency" of this management plan to ensure a consistent national level of public health protection. The results of this approach are illustrated through a case study at a well-studied South Florida recreational marine beach. This case study explores different monitoring targets based on two different health endpoints (skin versus gastrointestinal illness) and recommends a beach regulation program for the study beach that focuses predominately on source prevention.